Political polarization and selection in representative democracies - Dominik Duell; Justin Valasek (Journal of Economic Behavior & Organization, 2019)
While scholars and pundits alike have expressed concern regarding the increasingly “tribal” nature of political identities, there has been little analysis of how this social polarization impacts political selection. In this paper, we incorporate social identity into a principal-agent model of political representation and characterize the impact of social polarization on voting behavior. We show that identity has an instrumental impact on voting, as voters anticipate that political representatives' ex post policy decisions have an in-group bias. We also conduct a laboratory experiment to test the main predictions of the theory. In contrast to existing work that suggests social polarization may have a positive impact by increasing participation, we show that social polarization causes political representatives to take policy decisions that diverge from the social optimum, and voters to select candidates with lower average quality.
Keywords: C92; D72; 300; social identity; political selection; political polarization